PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Pangestuti, Dewi Cahyani; Hamidi, A. (Ekonomi dan Bisnis, 2016)
The development of a company's stock price reflects the value of the company's stock. Changes in stock prices is influenced by several factors, including the company's fundamentals. This illustrates the company's fundamentals internal state companies, which can be seen on the data derived from the financial statements of the company. The purpose of this study in order to determine the effect of independent variables simultaneously or partially to variable stock price and how much contribution. This research method using panel data or Pooled Data is a combination of time series data (over time) and cross section (between individuals / space) by using software Eviews 8. In this study the samples used were 41 companies with the observation period 5 years (2007-2011). The dependent variable is the Stock price and the independent variables are the Current Ratio (CR), Earning per Share (EPS), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR).The results of this study indicate that in partial EPS and DER significant effect on stock prices, while the variables CR and DPR did not have a significant effect on stock prices. Effect of CR, EPS, DER and DPR simultaneously to the stock price can be seen from the value of Adjusted R Square that is equal to 0.837975 This means that stock prices is explained by the CR, EPS, DER and DPR of 83.7975% and the remaining 16.2025 % explained by other variables such as the price earnings ratio, devident yield, net profit margin, return on assets, return on equity